What Kind of Accounting Standards Should the IASB Write? - Mary Tokar (Journal of Accounting and Management Information Systems (JAMIS), 2015)
This paper focuses on a long-standing challenge for standard setters: what kind of standards should they write? How specific and prescriptive should standards be? How should cost considerations influence requirements? How should standard setters balance comparability with effective communication of an entity's strategy and business model? What are reasonable expectations for the use of judgement? And what is the interaction of the types of standards with the training – both skills and subject matter knowledge – of accountants? These issues are explored using examples from recent IASB standard setting, primarily the IASB's new revenue standard. The author concludes that there is no single answer.
Keywords: M41; 650; IFRS; IASB; accounting standard-setting; financial statements; judgement; comparability; materiality; business model